Farmer Group Institution’s Typology and Agricultural Innovation Implementation Sustainability - Nurul Hilmiati (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2020)
Farmer group institutions have been being a target group for various innovations in the agricultural development program. Unfortunately, the aspect of their institutional system is getting ignored frequently. This study aimed to know the farmer group institution performance’s determinant factors and its effect on the agricultural innovation implementation sustainability. This was a longitudinal study using a qualitative approach involving ten farmer group institutions (mixed crop-livestock farming) done in Lombok island. The study showed that farmer groups with a good institutional system relatively performed a high level of sustainable innovation implementation in comparison with the group with a poor institutional system. There were four key factors affected the performance and the farmer group institution’s achievement: (1) strong leadership; (2) transparency; (3) regular group meeting; (4) and cash generating factor. The study also showed that farmer group institution which didn’t have those key factors tended to use the farmer group institution only to complete their physical need (impounded cows for security reason). It rarely uses to empower its group members. These conditions slowly could be developed as an individualistic treat on each group member that prevents the sustainable innovation implementation in the future. The agricultural innovation on this type of group usually only implemented in a short amount of time. Therefore, guidance for a good institutional system in a farmer group institution is required to be conducted to achieve a sustainable and comprehensive agricultural innovation implementation. Some strategies could be used to develop the four key factors to form a good institutional system in the farmer group institution.